Becoming us and them: Social learning and intergroup bias. Issue 4 (2nd April 2018) - Over, Harriet; McCall, Cade
Abstract: In recent years, research has demonstrated that the basic features of prejudice and discrimination emerge early in children's development. These discoveries call into question the role of social learning in intergroup bias. Specifically, through what means do we learn to distinguish "us" from "them?" Here, we explore this question, focusing on three key issues: how children respond to biased information they receive from others, how children selectively seek out certain types of biased information, and how children communicate biased information to others. We close by discussing the implications of this research for interventions to reduce stereotyping, prejudice, and discrimination.